Strategy of the Police Civil Servant Unit (Satpol PP) of Polewali Mandar Regency in Regulating Street Vendors: Case Study - Bonggasau, Eri; Ismawaty, Andi (Generasi Sains Indonesia, 2026)
This study aims to analyze the regulatory strategies implemented by the Civil Service Police Unit in managing street vendors in Wonomulyo District and to examine the factors influencing their effectiveness. A qualitative descriptive approach with a case study design was employed, using data collected through observations, in-depth interviews, and documentation. The findings reveal that street vendor regulation is carried out through a hybrid approach that integrates organizational enforcement, preventive measures, repressive actions, and post-relocation monitoring. The results indicate that strategies emphasizing dialogue, relocation, and structured organization are relatively effective in reducing conflict and improving compliance. However, their effectiveness is constrained by limited institutional capacity, weak socialization, and the economic dependence of street vendors on informal activities. The novelty of this study lies in its integrative analysis of regulatory strategies at the operational level, highlighting the interaction between enforcement, participation, and monitoring within a single governance framework. The study contributes to urban governance literature by proposing a context-sensitive regulatory model and offers practical implications for improving policy implementation in managing informal economies.